2013
DOI: 10.1113/jphysiol.2013.255968
|View full text |Cite
|
Sign up to set email alerts
|

TRPV3: time to decipher a poorly understood family member!

Abstract: The vanilloid transient receptor potential channel TRPV3 differs in several aspects from other members of the TRPV subfamily. This Ca 2+ -, ATP-and calmodulin-regulated channel constitutes a target for many natural compounds and has a unique expression pattern as the most prominent and important TRP channel in keratinocytes of the skin. Although TRPV3 is considered as a thermosensitive channel, its function as a thermosensor in the skin is challenged. Nevertheless, it plays important roles in other skin functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 79 publications
(131 reference statements)
2
93
0
Order By: Relevance
“…Nonetheless, TRPV1-mediated Ca 2+ influx might still be necessary for keratinocyte polarity and migration (Graham et al, 2013). TRPV3 is highly expressed in keratinocytes (Peier et al, 2002) and, through its wide range of functions, is purported to be one of the most important TRP channels in the skin (Nilius and Bíró, 2013;Nilius et al, 2014). A key role for TRPV3 in proliferation and differentiation of the epidermis is highlighted in Olmsted syndrome patients harbouring dominantly inherited TRPV3 mutations.…”
Section: Trpv Channelsmentioning
confidence: 99%
“…Nonetheless, TRPV1-mediated Ca 2+ influx might still be necessary for keratinocyte polarity and migration (Graham et al, 2013). TRPV3 is highly expressed in keratinocytes (Peier et al, 2002) and, through its wide range of functions, is purported to be one of the most important TRP channels in the skin (Nilius and Bíró, 2013;Nilius et al, 2014). A key role for TRPV3 in proliferation and differentiation of the epidermis is highlighted in Olmsted syndrome patients harbouring dominantly inherited TRPV3 mutations.…”
Section: Trpv Channelsmentioning
confidence: 99%
“…Interestingly, the levels of some kinds of AA metabolites, such as EET, 5,6-DHET, 8,9-DHET, LTB 4 , and 6-keto-PGF 1α , had a tendency to be different between these mouse strains in AA application groups. However, we did not find any correlation pattern between the degrees of ear edema and the amount of these metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV3 is a member of the vanilloid family of transient receptor cation channels 4 . Although the expression of TRPV3 is detected in brain, spinal cord, and dorsal root ganglion, it has been indicated to be highly expressed in skin, primarily in hair follicles and in keratinocytes that are present in the basal layer of the epidermis 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…TRPV3 can be also activated by camphor, thymol and 2-aminoethoxydiphenyl borate (2-APB). This channel plays a major role in regulating physiological skin homeostasis by regulating proliferation and apoptosis in epidermal keratinocytes (33). In addition, it has been reported that TRPV3 is involved in hairlessness combined with dermatitis (34).…”
Section: Trpv As Subfamily Of Trp Channelsmentioning
confidence: 99%